Clinical Implementation of Germ Line Cancer Pharmacogenetic Variants During the Next‐Generation Sequencing Era. Issue 3 (17th October 2013) - Gillis, N K; Patel, J N; Innocenti, F
<x xml:space="preserve">Abstract</x> More than 100 medications approved by the US Food and Drug Administration include pharmacogenetic biomarkers in the drug label, many with cancer indications referencing germ line DNA variations. With the advent of next‐generation sequencing (NGS) and its rapidly increasing uptake into cancer research and clinical practice, an enormous amount of data to inform documented gene–drug associations will be collected that must be exploited to optimize patient benefit. This review focuses on the implementation of germ line cancer pharmacogenetics in clinical practice. Specifically, it discusses the importance of germ line variation in cancer and the role of NGS in pharmacogenetic discovery and implementation. In the context of a scenario in which massive amounts of NGS‐based genetic information will be increasingly available to health stakeholders, this review explores the ongoing debate regarding the threshold of evidence necessary for implementation, provides an overview of recommendations in cancer by professional organizations and regulatory bodies, and discusses limitations of current guidelines and strategies to improve third‐party coverage. Clinical Pharmacology & Therapeutics (2014); 95 3, 269–280. doi:10.1038/clpt.2013.214